2020
DOI: 10.1371/journal.pone.0228538
|View full text |Cite
|
Sign up to set email alerts
|

“Wonderful! We’ve just missed the bus.” – Parental use of irony and children’s irony comprehension

Abstract: Irony is one of the linguistic means in which intended and expressed meaning diverge. It serves social-communicative functions, requires the understanding of the speaker's mental state and its comprehension takes place at an advanced stage of language acquisition. In the present study, we investigated 8-year old's irony comprehension and social skills and asked their parents about their preferred use of irony towards their children. We then compared children with the highest scores in irony comprehension test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
2
12
1
3
Order By: Relevance
“…Filippova (2014) compared Canadian and Czech children in their development of understanding irony and concluded that, particularly for ironic praise, socialization plays a role. Polish children have also been found to use and understand irony at young ages (8-years-old) and their proficiency was related primarily to their mothers’ usage (Banasik-Jemielaniak et al, 2020).…”
mentioning
confidence: 99%
“…Filippova (2014) compared Canadian and Czech children in their development of understanding irony and concluded that, particularly for ironic praise, socialization plays a role. Polish children have also been found to use and understand irony at young ages (8-years-old) and their proficiency was related primarily to their mothers’ usage (Banasik-Jemielaniak et al, 2020).…”
mentioning
confidence: 99%
“…For some children comprehension ability may start even earlier, when they are 3-4 years of age (e.g., Angeleri & Airenti, 2014;Loukosa & Leinonen, 2008;Recchia et al, 2010). However, this early comprehension is typically associated with higher use of ironic language in family environments (Angeleri & Airenti, 2014;Recchia et al, 2010;Banasik-Jemielniak, et al, 2020). At the early stage of comprehension, children first learn to understand that with irony speakers say something other than what they mean.…”
Section: Children's Irony Comprehensionmentioning
confidence: 99%
“…Around age 7 to 8, children start to understand the ironic speaker's intent (Glenwright & Pexman, 2010;Harris & Pexman, 2003;Pexman et al, 2005) and children's irony comprehension accuracy usually exceeds guessing-level (e.g., Banasik-Jemielniak, et al, 2020;Dews et al, 1996;Filippova & Astington, 2008;Köder & Falkum, 2021;Loukusa & Leinonen, 2008;Pexman et al, 2005). For example, Dews et al (1996) showed short clips from children's favourite television cartoon shows (e.g., Teenage Mutant Ninja Turtles, and The Little Mermaid) containing irony to 5-6-year-olds, 8-9-year-olds, and adults.…”
Section: Children's Irony Comprehensionmentioning
confidence: 99%
“…Irony has been studied by many research fields such as psychology [8], linguistics education [9], and computational science. It is used widely as an indirect negation in order to achieve different communication goals in many situations such as criticizing, make fun of people, and manipulate answers to upsetting questions.…”
Section: Introductionmentioning
confidence: 99%